Orthodontic management of a cleft lip and palate patient with anterior and posterior crossbite: A case report - Maria Laurentia Sanjaya; Ida Bagus Narmada; Natalya Indayani (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Cleft lip and palate (CLP) is a congenital craniofacial anomaly that results in a complex set of functional and aesthetic challenges. Patients with CLP often present with skeletal discrepancies, dental malocclusion, and crossbite due to maxillary deficiency. Successful management requires a coordinated multidisciplinary approach involving surgical, orthodontic, and restorative interventions. Purpose: The purpose of this case report is to demonstrate the challenges of complex CLP-related malocclusion and the benefits of coordinated care among specialists to achieve optimal outcomes. Case(s): This case report presents a 14-year-old patient with a repaired unilateral CLP, exhibiting both anterior and posterior crossbite and maxillary constriction. Clinical and radiographic evaluation revealed maxillary retrusion, asymmetrical dental arch form, and compromised occlusion. The treatment plan involved an interdisciplinary team approach. Case Management: The orthodontic treatment was carried out in four phases, beginning with alignment and leveling using self-ligating braces and posterior bite raising, followed by space creation with open coil springs and correction of anterior crossbite using Class III elastics. Final detailing and retention ensured optimal occlusion, improved aesthetics, and long-term stability. Conclusion: This case highlights the importance of a structured multidisciplinary approach in managing CLP patients with complex malocclusion. An integrated approach with orthodontic and other specialists is crucial to achieving functional occlusion, facial harmony, and long-term stability.